Kebijakan Otonomi Daerah: Otonomi Pendidikan dalam Perspektif Sosial Budaya - Achmad Fedyani Saifuddin (Antropologi Indonesia, 2001)
It unfortunately reveals that regional autonomy, and so to education autonomy as an integral part of it, as reflected through UU No.22 Tahun 1999 has not touched the very basic of cultural values and process of democracy, one core element it should significantly contain with. Central as well as regional policy makers and politicians, especially, have spent much their time to physical need and financial balancing debates between central and locals and deliberately forget the intrinsic cultural issue of the term, that is democracy as a cultural value formation process. Taking our current national education situation into account this article tries to introduce some cultural principles education autonomy should aim at. Based on holism in cultural approach education autonomy should pay attention seriously to strengthening community support to education.